Primary paraspinal hydatid cyst with intraspinal extension. A rare case report - Saman Anwar; Ayesha Shayan; Hina Naseer; Azzan Mujahid; Rabia Ahmed; Bushra Shamim (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2023)
Hydatid cyst is a zoonotic disease caused by Echinococcus granulosus. It rarely presents in the musculoskeletal system. Primary hydatid disease in paraspinal muscles is very rare. It can be discovered as an incidental finding in radiological imaging. Symptomatic patients are presented with usually symptoms secondary to the compression effect. It can cause dreadful consequences like erosion of adjacent bones, myelopathy, and cauda equine syndrome if left untreated. We present such a case of Primary Paraspinal Cyst with Intraspinal Extension, and its radiological imaging findings, including X-ray, CT scan, and MRI.